(untitled) (Physical Education, Health and Social Sciences, 2026)
Artificial egg incubation is important in poultry production as it controls the environmental factors on the development of embryos. Effective incubation requires a certain level of control over temperature, humidity, ventilation and egg turning. In this paper, the design and development of a semi-automated egg incubator with low cost but with standard incubation parameters mentioned in the existing literature is provided, and a dual-power (AC/DC) operating system is proposed as one of the changes. To assess experimentally, three temperature conditions were taken collectedly, i.e. T1 = 36.5 °C, T2 = 37.5 °C, and T3 = 38 °C and humidity and ventilation conditions maintained fixed. A W1209 thermostat was used to control temperature, and a water-tray-based approach with the help of forced air circulation was used to control humidity. The proposed system has an automatic inverter and battery backup unlike most of the current incubator designs that only use an AC power supply, allowing a continuous operation during power failures. When chicken eggs were experimentally tested, the hatching rate was approximately 80%. The proposed incubator has good reliability, low cost and high suitability in rural poultry farming and educational purposes.